(untitled) (Research, Society and Development, 2021)
Oral health care is considered a risky practice for COVID-19, mainly due to the generation of aerosols and proximity to the patient. Because of this, dental practice was changed in the face of the pandemic. Thus, the objective was to investigate the perceptions of dentistry students regarding fear and anxiety in relation to patient management and the risk of infection in the context of the COVID-19 pandemic. This is a cross-sectional study carried out with 167 undergraduate dentistry students from a university center in the interior of Ceará. Data collection was carried out between March and April 2021 by completing an online questionnaire subdivided into: sociodemographic data, assessment of fear and insecurity regarding dental care and assessment of anxiety symptoms, through the Anxiety Inventory of Beck. Data were then analyzed using the Statistical Package for Social Sciences (SPSS) 22.0, considering a 95% confidence level and significance of p<0.05. The average of the Beck anxiety scale was 18.84 (±12.88) and 61.1% of the students reported minimal/mild symptoms of anxiety. The presence of minimal/mild symptoms was related to possession of a belief/religion (p=0.039), lack of fear in caring for patients with suspected COVID-19 (p=0.003), absence of insecurity in returning to clinical practices (p=0.008). In short, most students had minimal/mild symptoms of anxiety, which was associated with less fear and insecurity in performing clinical practices and the presence of a religion.